Strengthening Public Financial Management : Exploring Drivers and Effects - Fritz, Verena (World Bank Group, Washington, DC, 2014)
This paper explores two relationships, first between country characteristics and the quality of public financial management ('drivers'), and second between the quality of public financial management systems and expected outcomes ('effects'). On the influence of country characteristics, the paper investigates economic factors (income level, growth, and resource dependency), population size, levels and sources of revenue, and three macro-political characteristics -- political stability, regime type, and the presence of programmatic parties. These characteristics jointly explain about 40 percent of the variation in the quality of public financial management across countries. Furthermore, first-difference analysis suggests that countries with lower initial public financial management quality improve at a higher rate over time. This implies that structural factors set the scene for the likelihood of better or worse performance, but also that there is substantial variation among countries sharing certain characteristics and reform opportunities exist even in unfavorable environments. Methodologically, a key limitation is that the direction of causality cannot be fully addressed with the types of data available. On the effects of the performance of public financial management, the paper finds evidence that stronger performance results in better budget credibility, but not in lower deficits. Furthermore, there is no clear evidence regarding operational efficiency. The observed disconnect could be caused by missing complementary state capacities, measurement problems, or other issues, which need to be explored further. Overall, the findings are consistent with the assumption that stakeholder incentives and constellations matter and that reform approaches combining good technical calibration and political economy considerations are likely to influence success in strengthening public financial management.